2010
DOI: 10.2147/ppa.s12461
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on antipsychotic treatments and their association with clinical outcomes

Abstract: This analysis examined patient-reported attitudes toward antipsychotic medication and the relationship of these attitudes with clinical outcomes and pharmacotherapy adherence. The analysis included three randomized, double-blind studies in patients with schizophrenia, schizoaffective disorder, or schizophreniform disorder diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders 4th Edition and randomly assigned to treatment with olanzapine 5-20 mg/day or another antipsychotic (haloperid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The critical importance of optimal adherence to prescribed antipsychotic treatments has been convincingly demonstrated in patients with schizophrenia [ 4 ]. Positive attitude towards medication, as measured by the DAI-10, is associated with significantly higher adherence rates [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…The critical importance of optimal adherence to prescribed antipsychotic treatments has been convincingly demonstrated in patients with schizophrenia [ 4 ]. Positive attitude towards medication, as measured by the DAI-10, is associated with significantly higher adherence rates [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also found that non adherence appears to be one of the factors most likely to increase the risk of relapse in schizophrenic patients [ 6 ]. Medication noncompliance and under-compliance continues to be a problem in the treatment of schizophrenia in the United States and Canada; the vast majority of hospital admissions for exacerbation of psychosis have been linked to noncompliance [ 12 ]. In Germany it has been found that patients who tend to experience a relapse are less likely to have a positive attitude toward treatment adherence [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antipsychotic medication compliance was expressed by patients and their care givers to be a strong protector of relapse. It was found that the relapse risk was substantially lower when a patient was adhering properly to the antipsychotic therapy [ 12 ]. Improvement in symptoms and the recognition of this improvement by patients may have led to improvement in their attitude to medication [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…20 , 31 Positive attitude towards medication, as measured by the DAI-10, is associated with significantly higher adherence rates. 32 , 33 The attitude towards treatment in outpatients has been additionally related to factors, such as employment status, duration of untreated psychosis (DUP), disease severity, treatment response, hospital profile, and therapeutic alliance with the medical staff. 7 , 26 , 27 , 34 , 35 Moreover, the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) study found that the degree of clinical improvement due to treatment and patient quality of life are factors also related to the attitude towards medication.…”
Section: Discussionmentioning
confidence: 99%